A 'forgettable minority'? Psychiatric Institutions and the Intellectually Disabled in Ireland, 1965–84. (25th May 2020) - Kilgannon, David
Abstract: This article investigates the admission of the intellectually disabled to institutional psychiatric facilities in the Republic of Ireland between 1965 and 1984, using this as a way to explore disability provision and the later years of the state's congregate mental hospital network. Drawing on institutional documents and news media, it argues that 'handicap admissions' continued along an established pattern, while demonstrating how these facilities remained ill-equipped to meet the needs of disabled residents. In doing so, this article begins to address the broader lacuna surrounding intellectual disability within Irish historiography, while complicating an emergent body of work on the 'deinstitutionalisation' of the state's psychiatric hospitals during the late twentieth century. It suggests ways in which institutional records can be used to access patient experiences and highlights the need for further research on intellectual disability, examinations of which can contribute towards the histories of institutionalisation and social policy in post-war Ireland.